Release from Retroactive Retention Interference for Acoustic Duration. (May 2014) - Ries, Dennis T; Gadd, Danielle; Smith, Meghan
Listener retention of stimulus duration was studied. Measures of difference-limen-for-duration (DLD) between standard and comparison stimuli were obtained for intervals with and without intervening noise bursts, including an intervening condition with a lateralization cue. The DLD was significantly higher when intervening sounds were present, but a lateralization cue mitigated the interference, presumably by allowing attention to be more readily allocated to retention of the standard. General interference results are in keeping with those reported for pitch, loudness, and timbre retention, but not for retention of gap length. Release from interference with a lateralization cue is akin to that reported for pitch. Overall, the ramifications of retroactive interference on duration retention are more similar to those reported for pitch than for another temporal-based attribute—namely, gap length.